2012
DOI: 10.1186/1475-2840-11-50
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and lipid management fall far short in persons with type 2 diabetes: results from the DIAB-CORE Consortium including six German population-based studies

Abstract: BackgroundAlthough most deaths among patients with type 2 diabetes (T2D) are attributable to cardiovascular disease, modifiable cardiovascular risk factors appear to be inadequately treated in medical practice. The aim of this study was to describe hypertension, dyslipidemia and medical treatment of these conditions in a large population-based sample.MethodsThe present analysis was based on the DIAB-CORE project, in which data from five regional population-based studies and one nationwide German study were poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
5
25
0
4
Order By: Relevance
“…This inconsistency of guidelines may contribute to possible overuse of ASA for primary prevention in T2DM in our study. Finally, it is necessary to mention that management of CV risk factors in diabetic patients is challenging and is regarded as unsatisfactory not only in Poland but also in other countries from EU and outside Europe [19][20][21][22][23][24]. Of note, it was observed by Polish researchers [25] that control of CV risk factors was better in CAD patients than in diabetic patients, although still unsatisfactory in most of them; it shows that DM is still not perceived as dangerous and life-threatening as CAD.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency of guidelines may contribute to possible overuse of ASA for primary prevention in T2DM in our study. Finally, it is necessary to mention that management of CV risk factors in diabetic patients is challenging and is regarded as unsatisfactory not only in Poland but also in other countries from EU and outside Europe [19][20][21][22][23][24]. Of note, it was observed by Polish researchers [25] that control of CV risk factors was better in CAD patients than in diabetic patients, although still unsatisfactory in most of them; it shows that DM is still not perceived as dangerous and life-threatening as CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in other countries also showed that most diabetic patients do not meet their HbA1c, BP and lipid treatment goals [20][21][22][23][24][25][26]. The most recent survey in U.S. patients [26] showed improvements in diabetes control over 12 years, but only 14% of patients met all their treatment goals (HbA1c ≤ 7% and individualised goals, BP < 130/80 mm Hg and LDL-cholesterol < 100 mg/dL and < 70 mg/dL in those with CHD) and achieved non-smoking status, which is slightly better than in our study (8%).…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Kituose tyrimuose hipertenzijos dažnis diabetu sergantiems pacientams panašus -svyruoja 50-83 proc. ribose [8,9,11,17,21]. Hipertenzija dažniausiai gydyta renino-angiotenzino sistemą slopinančiais vaistais: AKFI skirti 63,9 proc., ARB -24,3 proc.…”
Section: Cukrinio Diabeto Priežiūra Ir Komplikacijų Išaiškinimasunclassified
“…pacientų. Šie preparatai rekomenduojami kaip pirmo pasirinkimo vaistai gydant hipertenziją diabetu sergantiems ligoniams, taip pat dažniausiai skiriami ir kitose šalyse [8,17]. Atkreiptinas dėmesys, kad daliai pacientų AKFI skirti su ARB, nors arterinės hipertenzijos gydymo gairėse toks derinys nerekomenduojamas.…”
Section: Cukrinio Diabeto Priežiūra Ir Komplikacijų Išaiškinimasunclassified
See 1 more Smart Citation